2013
DOI: 10.1016/j.biochi.2013.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between indole-3-acetic acid (IAA) with a lectin from Canavalia maritima seeds reveal a new function for lectins in plant physiology

Abstract: Indole-3-acetic acid (IAA) bound is considered a storage molecule and is inactive. However, some studies have proposed an additional possible regulatory mechanism based on the ability of lectins to form complexes with IAA. We report the first crystal structure of ConM in complex with IAA at 2.15 Å resolution. Based on a tetrameric model of the complex, we hypothesize how the lectin controls the availability of IAA during the early seedling stages, indicating a possible new physiological role for these proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 63 publications
0
9
0
1
Order By: Relevance
“…Indole-3-butyric acid is known to be the most stable form of natural auxins; however, like tryptophan (Trp), indole-3-acetic acid (IAA), and indole-3-propionic acid (IPA), IBA is degraded aerobically depending on many factors, including the oxygen level and exposure to heat and light. [41][42][43][44] In this study, we determined how light accelerated the abovementioned decomposition (the methodology is described in the ESI †). The intensity of the maximum absorption for IBA in acid or anionic forms (l max ¼ 221 nm) decreased aer only 7 days in prepared water solutions exposed to stable visible light ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indole-3-butyric acid is known to be the most stable form of natural auxins; however, like tryptophan (Trp), indole-3-acetic acid (IAA), and indole-3-propionic acid (IPA), IBA is degraded aerobically depending on many factors, including the oxygen level and exposure to heat and light. [41][42][43][44] In this study, we determined how light accelerated the abovementioned decomposition (the methodology is described in the ESI †). The intensity of the maximum absorption for IBA in acid or anionic forms (l max ¼ 221 nm) decreased aer only 7 days in prepared water solutions exposed to stable visible light ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As both acidic and ionic forms of IBA degrade, the likely degradation product is 5-(2-formamidophenyl)-5oxopentanoic acid, a KYN derivative. [41][42][43][44] The light stability of the aqueous solutions was strongly correlated with the form of IBA and the type of cation or second binary mixture component in the products. Products 1, 2, and 5 were less stable than IBA and binary mixtures 3 and 4 under light exposure.…”
Section: Resultsmentioning
confidence: 99%
“…However, the phenotype (dwarf and more branches) of the GsSRK-t transgenic alfalfa is similar to the application of IAA. Furthermore, it is reported that lectins could interact with IAA, and possibly lectin controls the availability of IAA during early seedling stages ( Edelman and Wang, 1978 ; Delatorre et al, 2013 ). Another research also reported that an S-locus LecRLK in Arabidopsis AtARK2 was required for auxin-mediated lateral root development under phosphate-starved conditions ( Deb et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Los AH se han relacionado con la estimulación de la producción y elongación de raíces, lo que a su vez repercute en los procesos que definen la arquitectura de la raíz, la toma de agua, nutrientes y las asociaciones que establece la planta con los microorganismos del suelo en la rizósfera y que adicionalmente, pueden afectar diferentes rutas del metabolismo vegetal e influir sobre la arquitectura total de la planta (Canellas y Olivares, 2014;. Por otra parte se sabe que el ácido indol acético (AIA) puede establecer interacciones hidrofóbicas con otros compuestos (Delatorre et al, 2013), además, a través del proceso de humificación los microorganismos del suelo contribuyen preferencialmente a la formación de SH hidrofóbicas, por lo tanto este hecho podría favorecer la interacción de las SH con el AIA presente en el suelo, que luego podría ser utilizado por la planta. Sobre este aspecto, Nardi et al (2017) señalan la posibilidad de que la bioactividad de las SH se deba a la presencia de moléculas de auxinas atrapadas en la supraestructura húmica.…”
Section: Introductionunclassified